A new species of Filarinema Mönnig, 1929 (Nematoda: Trichostrongylidae) parasitic in the stomach of the western scrub wallaby, Notamacropus irma (Jourdan), in Western Australia. Issue 2 (3rd July 2019) - Beveridge, Ian
ABSTRACT: Filarinema chiltoni sp. nov. is described from the pyloric stomach of the western scrub wallaby or black-glove wallaby, Notamacropus irma (Jourdan) from Western Australia. The new species differs from most congeners in possessing two rather than three branches of the distal spicule, and from the few species that possess two spicular branches, in the morphology of the spicules and the inflation of the cuticle on the right side of the body.